Hip & Spine Mechanics - Understanding the linkage from several perspectives of injury mechanisms to rehabilitation using biomechanical modelling - Cambridge, Edward Douglas John (University of Waterloo, 2020)
One recent megatrend in medicine is that of “precision medicine” whereby a precise diagnosis leads to a precise intervention for superior results. This thesis was undertaken to enhance the understanding of spine and hip interactions and facilitate precision in both detection and the intervention of mechanical and neurological based disorders. The hip and spine are highly integrated structures. In order to adequately examine and improve the understanding of the complex mechanical linkage between the two, development of a highly biofidelic Hip-Spine Model (HSM) was pursued. Given that no model existed that incorporated the necessary detail, several challenges regarding model development needed to be addressed. It was clear that biofidelity of the model depended on a better understanding and representation of the passive hip stiffness in both males and females. Thus, the experimental data of passive stiffness was evaluated in conjunction with the HSM passive stiffness model predictions. Next, known Anterior Cruciate Ligament (ACL) injury risk factors, such as dynamic knee valgus (DKV) were examined in a female population where both the kinetic and kinematic variables of the hip and spine were evaluated to assist in differentiating those deemed at-risk and not-at-risk during the drop vertical jump (DVJ) procedure. Finally, an atlas of rehabilitation exercises was constructed to guide program design and progression/regressions of rehabilitation protocols for those with back and hip concerns. Each of these themes were unified around the overall goal of this thesis, that being the understanding of the hip-spine mechanical linkage pertaining to injury mechanisms and a guide for rehabilitation of hip-spine disorders. The first task was the development of the HSM. This model is anatomically detailed and driven by biological signals obtained from the individual to provide new insights into the understanding of the linkage in a way that was sensitive to the unique movement strategies of the individual. The HSM is an expansion of the previously established ‘Spine Model’ (SM), developed by Stuart McGill and his team over the past 37 years. The model anatomy was expanded from the current SM using the most complete single subject lower limb data set available know as the Twente Lower Extremity Model (TLEM). Hip ligaments were also added to enhance the passive behaviour of the model. An electromyographic (EMG) driven approach with subject specific kinematics was used to compute the model outputs that consisted of tissue and joint loads. Thus, the first objective of this thesis was to examine the interactions of hip and spine mechanics using a newly developed Hip-Spine Model (HSM) and then to investigate a spectrum of injury mechanisms and rehabilitation exercises. The next objective was to evaluate passive hip stiffness to enhance the biofidelity of the model and the understanding of hip mechanics in both males and females. A novel testing apparatus was designed and fabricated for measuring hip stiffness which could easily be adapted to clinical settings. This study also serves to establish normative baselines for passive hip stiffness in vivo. The third objective of this thesis was to examine issues of normal function and potential injury mechanisms. For example, ACL injury risk has been linked with some knee kinematic and kinetic patterns however, hip and spine interactions have not been appropriately explored nor have neuromuscular control strategies. This thesis linked the mechanical variables which differentiate at-risk landings of the DVJ task versus non-at-risk landing in females to enhance the understanding of risk behaviours. Clear differences in hip and spine control were documented to differentiate high and low valgus landings. Adding this knowledge to the current understanding of ACL injury risk will lead to the development of superior and more specific coaching cues to decrease tissue stress/strain concentrations. This approach will underpin intervention strategies leading to lower risk behaviour and correspondingly lower injury risk among female athletes. The final objective of this thesis was to evaluate the appropriateness of rehabilitation exercises to address hip spine disorders. Currently, there exists a myriad of exercises but little evidence to guide clinical reasoning or decisions for exercise choice, progression, volume and technique. Currently missing from the literature is knowledge of tissue and joint loads in combination with muscle activation patterns. This knowledge will facilitate better matching of specific exercises for specific disorders. The main objectives of this thesis were: (1) The development of the anatomically detailed, biologically driven HSM which successfully computes joint and tissue loads unique to the individual and their neuromuscular control strategy. (2) The establishment of passive hip stiffness for males and females. (3) To enhance understanding of both neurological and tissue loading characteristics associated with ACL injury risk which when added to the current knowledge provides the opportunity for more precise interventions. (4) The beginning of the development of an atlas for rehabilitation exercises to guide prescriptions that can be matched to specific hip-spine disorders. These findings have the potential to enhance precision medicine in the area of musculoskeletal health – where precision medicine is currently lacking.
Keywords: spine; hip; biomechancis; modelling; rehabilitation; exercise; injury mechanism